Business Opportunity: Chocolate Cupcake Beauty Blender / Noranisya Nasaruddin - Nasaruddin, Noranisya (2021)
Nowadays, we know that business is one of the major sources of income for human since the early ages of civilization. Even the Prophet Muhammad once said, “9/10 of income come from businesses”. Therefore, business has a big potential to increase one social standard and living. For my business, that I prepared for this selling project is about chocolate cupcake beauty blender. This chocolate cupcake beauty blender materials are sponge and the application area is face. Its weight is 0.09 kg, the size is 4 X 6 cm which is very light. This beauty blender also lasts anywhere from 3 to 6 months, depending on how well the users take care of it. The colour of it is dark brown. This beauty blender is a versatile makeup sponge that can be used for practically anything in makeup bag such as foundation, BB cream and concealer. I choose this chocolate cupcake beauty blender for my business project because I am one of the users. So, this is easier for me to promote because I can prove to other customers with my own. I just used RM30 as my modal. My achievement for this project is RM232 start from 1 May 2021 to 1 June 2021. With this report I will show all activities throughout the sales of this business that I run. In terms of project description before activity, project outcome after activity and experience in sell this chocolate cupcake beauty blender to achieve my sales targets. I decided to sell this product because this is one of the makeup tools that every people love. Not just women but also men. This product also has a higher request in makeup market now.